Kritik Islam Progresif terhadap Formalisasi Agama: Studi Pemikiran Farish A. Noor - Nur Sidik (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This article examines Farish A. Noor's progressive Islamic thought as a critique of the formalization and bureaucratization of religion in the socio-political context of Southeast Asia. Islam is understood not merely as a normative institution, but as a system of ethical and humanistic values with an emancipatory function. This research uses a qualitative approach through thought analysis to explore the intellectual background, socio-political context, and characteristics of Farish A. Noor's progressive Islamic ideas. The results indicate that his thoughts emerged as a response to state domination over religion, religious conservatism, and the hegemony of official interpretations that undermine critical thinking among the people. Through reinterpreting the concept of "radical" in its historical and transformative sense, Farish affirms Islam's commitment to justice, freedom, and human dignity. This study also finds that Farish A. Noor's progressive Islamic ideas are relevant to the Indonesian context, particularly within the Islamic tradition, which is inclusive, pluralistic, and oriented towards social progress.